PENGEMBANGAN SIKAP SOSIAL DENGAN METODE BERMAIN BAGI ANAK TAMAN KANAK-KANAK - Serli Marlina (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study aims to determine the development of social attitudes using play methods. This type of research is literature study. The method used is the study of literature, data collection techniques by conducting a study of the review of books, literature, records, and reports related to the problem being solved. Researchers conduct studies relating to theories related to the research topic, gathering as much information from the literature relating to the development of social attitudes with play methods. The result is social behavior namely imitating behavior, competitive behavior, cooperation, sympathy, empathy, social support, sharing, and familiar behavior. All of these behaviors are developed through play. For that the dimensions of the game that can develop children's social abilities are as follows: (1) Playing solitary, meaning playing alone without friends (2) Playing in parallel, meaning that the activity of playing is done by a group of children using the same plaything but each children play alone, (3) Play associatively means that children play in the same game and with the same rules, (4) Play cooperatively means that each child has a certain role in order to achieve the goal of playing. The game used can be traditional games or games that are assisted by learning media and other educational games